Dark survival in a warming world - Andrew McMinn; Martin, AR (2013)
Most algae regularly experience periods of darkness ranging from a few hours to a few days. During this time, they are unable to photosynthesize, and so must consume stored energy products. However, some organisms such as polar algae and some microalgal cysts and spores are exposed to darkness for months to years, and these must use alternative strategies to survive. Some taxa, such as dinoflagellates, form cysts and become dormant. Others use physiological methods or adopt mixotrophy. The longest documented survival of more than a century was for dinoflagellates buried in sediments in a Norwegian fjord. Seasonal changes in daylight hours are naturally unaffected by climate change. This means that polar microalgae will in the future need to survive the same period of seasonal darkness but at higher temperatures, and this will require a greater drawdown of stored energy. Recent experimental work has shown that both Arctic and Antarctic phytoplankton are able to survive increases of up to 68C in the dark.